Epidemie i choroby jako obraz nieszczęścia w religijnej literaturze w metropolii kijowskiej w XVII wieku - Nowak, Alicja Z. (Studia Ukrainica Posnaniensia, 2023)
Multilingual Ruthenian literature in the 17th century reflects the problems with disasters, mainly wars, which resulted in hunger and disease, often turning into epidemics. They harassed society devastatingly, causing fear and despair. Teachers, especially those from monastic circles, tried to channel these anxieties towards piety, religious activity and prayer practices. Therefore, they described misfortunes as signs sent by God, who desires human conversion. The existence of the intercession of saints was recalled, and works were published in which their effective intercession with God for people was popularized. The sermons and collections describing miracles, treated as testimonies, probably had a special motivating meaning. The works were written in Ruthenian and Polish, thus they were available to a wide range of citizens of a multinational state. In this way, pastoral goals were realized in relation to the Orthodox and Uniates, but the goal was also a more widely addressed (Roman Catholics, Protestants) apology of faith.